2023
DOI: 10.1080/19490976.2023.2178805
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic cell transplantation, the microbiome, and graft-versus-host disease

Abstract: Many patients with hematological malignancies, such as acute myeloid leukemia, receive an allogeneic hematopoietic cell transplantation (HCT) to cure their underlying condition. Allogeneic HCT recipients are exposed to various elements during the pre-, peri- and post-transplant period that can disrupt intestinal microbiota, including chemo- and radiotherapy, antibiotics, and dietary changes. The dysbiotic post-HCT microbiome is characterized by low fecal microbial diversity, loss of anaerobic commensals, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 112 publications
(111 reference statements)
1
8
0
Order By: Relevance
“…Furthermore, subgroup analyses found an association between lower intestinal diversity and higher risks of transplantation-related death and death attributable to GVHD . While the observational nature of the study by Peled et al introduces risk of biases—patients who were more severely ill may have had more cancer therapy, more health care, and more antibiotic exposure and thus were at higher risk of worse outcome, including mortality after allo-HCT—these findings were consistent with prior studies and the current understanding of the pathogenesis of microbiome injury …”
supporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, subgroup analyses found an association between lower intestinal diversity and higher risks of transplantation-related death and death attributable to GVHD . While the observational nature of the study by Peled et al introduces risk of biases—patients who were more severely ill may have had more cancer therapy, more health care, and more antibiotic exposure and thus were at higher risk of worse outcome, including mortality after allo-HCT—these findings were consistent with prior studies and the current understanding of the pathogenesis of microbiome injury …”
supporting
confidence: 77%
“…5 While the observational nature of the study by Peled et al 5 introduces risk of biases-patients who were more severely ill may have had more cancer therapy, more health care, and more antibiotic exposure and thus were at higher risk of worse outcome, including mortality after allo-HCT-these findings were consistent with prior studies and the current understanding of the pathogenesis of microbiome injury. 6,7 The results from the study by Rashidi et al 1 improve our understanding of the deleterious association of gut microbiota disruption with the development of aGVHD and contribute to risk vs benefit assessments in antibiotic prescribing. These findings 1 pave the way for designing and evaluating future antimicrobial stewardship interventions aimed at tailoring antibiotic regimens to minimize potential harms and maximize likelihood of benefits in patients undergoing allo-HCT.…”
Section: + Related Articlementioning
confidence: 99%
“…While statistical differences were not observed in this clinical trial, it still acknowledges the positive value of FMT in the context of HSCT. 118 , 119 Van den Brink’s lab explored the value of the intestinal microbiota in recipient hematopoietic system reconstruction after bone marrow transplantation. They found that in mice lacking intestinal microbiota, there is impaired hematopoietic system reconstruction after bone marrow transplantation.…”
Section: Targeting Gut Microbiota To Regulate Hematopoiesismentioning
confidence: 99%
“…Future research should include mechanistic and interventional studies to explore the microbiome’s role in lymphoma responses and improve treatment outcomes ( 57 ). The success of fecal microbiota transplantation in other contexts provides evidence that the microbiome can be targeted for therapeutic intervention ( 69 ), Davar et al. ( 23 ).…”
Section: Adoptive Immunotherapymentioning
confidence: 99%
“…Microbe-free formulations of probiotics may also be used. Immunotherapy can be combined with prebiotics, probiotics, postbiotics, and symbiotics in upcoming immune-oncology trials ( 69 ). The completed clinical trials testing the effect of probiotics on cancer immunotherapy is listed in Table 1 .…”
Section: Adoptive Immunotherapymentioning
confidence: 99%